Discover new information and insights with the help of IDNLearn.com. Find in-depth and accurate answers to all your questions from our knowledgeable and dedicated community members.
Sagot :
Since [tex]f(6)=0[/tex], by the remainder theorem this means that x - 6 divides f(x) exactly. This means there are constants a, b, and c such that
[tex]\dfrac{f(x)}{x-6} = ax^2 + bx + c[/tex]
Multiplying both sides by x - 6 gives
[tex]f(x) = (x-6)(ax^2+bx+c) \\\\ 2x^3-19x^2+45x-18 = ax^3 + (b-6a)x^2 + (c-6b)x - 6c[/tex]
Then a, b, c satisfy
[tex]\begin{cases}a=2 \\ b-6a=-19 \\ c-6b=45 \\ -6c=-18\end{cases}[/tex]
and solving this system gives a = 2, b = -7, and c = 3.
So, we have
[tex]2x^3-19x^2+45x-18 = (x - 6) (2x^2 - 7x + 3)[/tex]
The quadratic term can be factored as
[tex]2x^2 - 7x + 3 = (2x - 1)(x - 3)[/tex]
which leaves us with
[tex]f(x) = (x-6)(2x-1)(x-3)[/tex]
so that the zeros of f(x) are 6, 1/2, and 3.
We appreciate your contributions to this forum. Don't forget to check back for the latest answers. Keep asking, answering, and sharing useful information. Thank you for choosing IDNLearn.com. We’re dedicated to providing clear answers, so visit us again for more solutions.